Prelacteal feeding practice and its associated factors among mothers of children age less than 24 months old in Southern Ethiopia - Esayas Aydiko Amele; Birhanu wondimeneh Demissie; Kalkidan Wondwossen Desta; Emebet Berhane Woldemariam (BMC, 2019)
Abstract Background Although Pre-lacteal feeding is a barrier for implementation of optimal breastfeeding practices and increases the risk of neonatal illness and mortality, still it is continued as a deep-rooted nutritional malpractice in developing countries. In Ethiopia pre-lacteal feeding continued as one of the nutritional malpractices in newborns. Therefore the aim of this study was to assess pre-lacteal feeding practice and its determinants among mothers of children less than 24 months of age in Sodo zuria district, Wolaita zone, Southern Ethiopia. Methods Community-based cross-sectional study was conducted from February 15, 2017 to March 12, 2017 in Sodo zuria district, Wolaita zone, Southern Ethiopia. Five hundred five (505) mothers of children aged less than 24 months were selected by multistage randomized sampling technique and the data were collected by using interview based structured questionnaire. Descriptive statistics, binary and multivariable logistic regression analysis were employed to identify the factors associated with pre-lacteal feeding practices. Variables with a p-value < 0.05 were identified as statistically significant factors. Results The prevalence of pre-lacteal feeding practice was 20.6%. The common type of pre-lacteal feeding given was plain water; 38(7.7%) and the major reason was insufficient breast milk 32(6.5%). Mothers living with extended family type (AOR = 10.64, 95% CI: 1.05, 10.71), Lack of breastfeeding counseling (AOR = 5.16, 95% CI: 1.76, 15.13) and mothers who avoid colostrum (AOR = 9.72, 95% CI: 3.46, 27.30) were statistically significant positive predictors of pre-lacteal feeding practice. Conclusion & Recommendation Pre-lacteal feeding is commonly practiced in Soddo zuria district. Mothers who live with extended family type, mothers who did not get breastfeeding counseling and mothers who avoid colostrum were statistically significant positive predictors of pre-lacteal feeding practice. Therefore, strengthening breastfeeding counseling about the risks associated with pre-lacteal feeding and colostrum feeding intervention should be integrated. Promotion of intensive nutrition education program, on the benefit of colostrum by giving special emphasis to extended family mothers should be implemented in the community.